Where he left me : a novel - Baart, Nicole (Atria Paperback, 2025)
""In every world, I'd find you." Sadie Sheridan's new husband Felix, a professor of planetary sciences, has vowed to never leave her. But when Felix doesn't return from a work trip, Sadie is stranded at Hemlock House, the remote mountain homestead where her husband grew up. Doubt creeps into Sadie's heart. Then panic. Where is he? Scared and alone in a place that feels haunted, Sadie struggles to make sense of what her missing husband left behind. But when she catches strangers lurking around the property, Hemlock House instantly becomes both a sanctuary and a prison. Navigating threats from outside and in, Sadie is forced to confront shocking secrets that leave her questioning whether she really knows Felix at all. As a powerful storm bears down, she must decide: is she fighting only for her own survival now-or for the man who promised her the stars?"